PENGGUNAAN ALAT PERAGA PUZZLE DENGAN METODE DEMONSTRASI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI MI KEBOKICAK - Nadiroh, Intan; Utami, Sri (LP2M STAI Darul Kamal NW Kembang Kerang, 2022)
Abstract This research is motivated by the lack of students' learning motivation in the material of flat shapes. The low motivation of these students is indicated by the lack of student attention to the subject matter so that there are still many students who are often wrong in determining the kinds of flat shapes. In addition, the supporting facilities and teaching aids at MI kebokicak are still very minimal. One of the efforts so that the level of student learning motivation becomes better is to use puzzle props with the demonstration method which is expected to have a good effect on students' motivation in building data material. The purpose of this study was to increase students' motivation to work on the material of flat shapes using puzzle props with the demonstration method in class III students in the second semester of MI Kebokicak. The research was carried out using a quantitative research method of multiple regression type and classical assumption test with the help of SPSS 20 for windows using random sampling technique. The focus of this research is to find out; a) is there any effect of puzzle teaching aids on students' learning motivation, b) is there any effect of demonstration method on students' learning motivation and c) is there any effect of puzzle teaching aids with demonstration method on students' learning motivation. This can be seen from the results of calculations using the t-test and f-test, with the following details; a) there is a significant effect between puzzle props on students' learning motivation, this can be proven by the results of the partial test output (t) obtained t count (2,381) shows t count > t table that is (2,028) thus t count is greater from the t table and the standard of significance/probability value (a) (0.023 < 0.050), b) there is a significant effect between the effect of the demonstration method on students' learning motivation, this can be proven by the results of the partial test output (t) obtained t count ( 2.775) shows arithmetic > t table, namely (2.028) thus t arithmetic is greater than t table and the standard of significance / probability value (a) (0.000 < 0.050), c) there is a significant effect between the influence of puzzle props and the demonstration method on student learning motivation, this can be proven by the results of the hypothesis test table simultaneously, the F table calculation is carried out using the formula (F table = N-m-1 = db39-2-1 = db36 with k level trust 5%), then obtained F table = (3,26). The result of the above analysis is that the calculated F value = (12.126), shows F arithmetic > F table (16.665 > 3.26) and the standard of significance/ probability value is (0.000 < 0.05).